Prognostication and Proactive Planning in COVID-19 - Newport, Kristina B. (J Pain Symptom Manage, 2020)
Accurate prognostication is challenging in the setting of SARS-CoV-2, the virus responsible for COVID-19, due to rapidly changing data, studies that are not generalizable, and lack of morbidity and functional outcomes in survivors. To provide meaningful guidance to patients, existing mortality data must be considered and appropriately applied. Although most people infected with SARS-CoV-2 will recover, mortality increases with age and comorbidity in those who develop severe illness.